The Place of Histochemical Stains for Differential Diagnosis in Duodenal Biopsies - Ebru Altındal Susem; Mehtap Eroğlu; Elif Acar; İrfan Bayram (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2021)
The biopsy is the primary examination method in diagnosing duodenal pathologies and Gluten enteropathy that can cause symptoms such as gas, diarrhea, weight loss, anemia, osteoporosis. Allows monitoring of response to therapy. Histochemical studies are inevitable in specific findings such as reactive changes, giardia, subepithelial collagen thickening, fibrosis, and gastric metaplasia. We aimed to understand the contribution of histochemical applications to differential diagnosis and to show their superiority compared to hematoxylin-eosin sections in routine use by simultaneously making histomorphological evaluations on hematoxylin and eosin sections. This research is a retrospective study conducted in 2011, using the archives of Yüzüncü Yıl University, Faculty of Medicine, Department of Pathology, between 2001-2010. Ten normal, 50 Gluten enteropathy and 50 duodenitis samples; Along with histopathological examinations, we applied Masson Trichrome, Periodic acid-Schiff, Periodic acid-Schiff with diastasis, Periodic acid Schiff-Alcian Blue, High Iron Diamine-Alcian Blue. Chi-square, likelihood ratio tests, and SPSS (ver: 13) statistical package program used. We detected microscopic findings parallel to diagnostic criteria. While the number of goblet cells and intraepithelial neutrophils did not differ in the groups (P =0.176 and P=0.096), there was a significant variation in the intraepithelial lymphocyte count (P=0.010). The frequency of flattening and blunting of the villi, crypt hyperplasia, and Brunner gland hyperplasia were significant in gluten enteropathies (P=0.000). Conclusion We could not find any difference in specific pathologies associated with histochemical studies in our group, so hematoxylin-eosin sections are more valuable in the differential diagnosis.